New DSM-5 PTSD guilt and shame symptoms among Italian earthquake survivors: Impact on maladaptive behaviors. (May 2017) - Carmassi, Claudia; Bertelloni, Carlo Antonio; Gesi, Camilla; Conversano, Ciro; Stratta, Paolo; Massimetti, Gabriele; Rossi, Alessandro; Dell'Osso, Liliana
Abstract: Important changes were introduced concerning posttraumatic-stress disorder (PTSD) by the DSM-5 recognizing the role of negative emotions such as guilt and shame, but little evidence is yet available on their prevalence in population assessed by means of DSM-5 criteria. In this study we explored the rates of guilt and shame DSM-5 PTSD diagnostic symptoms among Italian survivors to a massive earthquake and their possible correlation with PTSD and maladaptive behaviors. 869 residents of the town of L'Aquila exposed to the earthquake of April 6th, 2009 were investigated by the Trauma and Loss Spectrum-Self Report (TALS-SR) with particular attention to guilt and shame feelings. DSM-5 symptomatological PTSD was reported by 41.7% of survivors, further 11.6% endorsed at least one guilt/shame symptoms, with significantly higher rates of endorsement were in PTSD respect to No-PTSD subjects, and in the subgroup with at least one maladaptive behavior respect to those with none. There was a significant main effects of PTSD and at least one guilt/shame symptom on TALS-SR symptomatological domains. Mean TALS-SR Maladaptive coping domain score appeared significantly higher in the subgroup with at least one guilt/shame symptom. Further study are needed to investigate guilt and shame feelings in survivors to a natural disaster. Highlights: 41, 7% of the sample presented a PTSD diagnosis. 11, 6% reported at least a guilt and shame symptom. Guilt and shame symptoms were reported more frequently in survivors with PTSD. Guilt and shame were related significantly to PTSD symptoms and maladaptive coping.